Principles and techniques of practical biochemistry - Wilson, Keith;Ed. Walker, John M;Ed (Cambridge University Press, 1994)
This new edition of a biochemistry text introduces the student to the basic principles of techniques which are routinely used in modern biochemistry. It gives greatest attention to those techniques which undergraduate biology and biochemistry students encounter in practical classes.